The Need to Develop a Fast-track-based Bahasa Indonesia Learning Model in Higher Education Institutions - Hariadi, T; Suwandi, S; Slamet, St Y; ., Sumarwati (KnE Social Sciences, 2018)
Research on the theme of the development of a Bahasa Indonesia fast-track-based learning model has never been done by other researchers. This study focuses on the involvement of lecturers and students by prioritizing the improvement of the quality and quantity of learning through various learning tracks that can accelerate the students’ understanding and learning outcomes. This research is an exploratory study that aims to: (1) describe the condition of Bahasa Indonesia learning in colleges; and (2) describe the need for the best Bahasa Indonesia learning model for lecturers and students. The research subjects in this study were the lecturers and students of the colleges in Pontianak city. The methods used to collect the data were documentation, observation, a questionnaire, and interviews. The collected data were then analyzed using a descriptive method. The results of this study are as follows: (1) the learning quality of Bahasa Indonesia in Pontianak city is not yet maximal due to the use of conventional methods and the lack of a feasible learning model; (2) there is a need for the fittest Bahasa Indonesia learning model for both lecturers and students in order to enhance contribution, participation, and improvement in the application of a track-based learning model. Keywords: Bahasa Indonesia, development, fast track, learning model.